From Assessment to Automation: A Blueprint for Human Services Program Modernization. - Aguilar, Pat (Policy & Practice (19426828))
The article focuses on the modernization of public human services programs through automation, optimization, and workforce model improvements. It emphasizes the importance of streamlining processes to minimize rework and enhance efficiency, advocating for a thorough program assessment to identify bottlenecks and inefficiencies. Key steps include collecting data, mapping processes, analyzing results, and making informed decisions to re-engineer operations. The article also highlights the role of smart automation in routine tasks, using examples of successful implementations to illustrate potential benefits for program delivery.